Correlation of metabolic syndrome with clinicopathological characteristics and treatment outcome in bladder cancer : a retrospective observational study - Yong, KL; Nurul Amniyyah A; Yogaambikai P; Shanggar K; Syireen A; Noorasyikin S; Amira Hajirah AJ; Nur Akmarina M. Said (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
The relationship between metabolic syndrome (MetS) with the clinicopathological characteristics, chemotherapy responsiveness and survival outcome in bladder cancer is under-investigated and often conflicting. We retrospectively analysed data of 45 patients who were diagnosed with non-muscle invasive bladder cancer (NMIBC) or muscle-invasive bladder cancer (MIBC) and received chemotherapy at the University of Malaya Medical Centre (UMMC) between 2010 and 2020. Overall, 24 patients (53.3%) were presented with MetS criteria at the time of diagnosis. Across MetS and its components, no significant association was found with tumour pathological stage, histological grade, and chemotherapy response in our patient population. Interestingly, there was a significant difference in overall survival between patients with and without diabetes (62.47 + 8.32 months and 84.93 + 3.96 months respectively, p=0.045). Although no significant association between MetS with bladder cancer clinicopathological characteristics and treatment outcome was found, intensive care and lifestyle modification should be considered for bladder cancer patients with metabolic disorders.